Multi-Omics Analysis Reveals Anti-Staphylococcus aureus Activity of Actinomycin D Originating from Streptomyces parvulus - Yuqi Lin (MDPI AG, 2021)
Staphylococcus aureus (S. aureus) is a common pathogen that causes various serious diseases, including chronic infections. Discovering new antibacterial agents is an important aspect of the pharmaceutical field because of the lack of effective antibacterial drugs. In our research, we found that one anti-S. aureus substance is actinomycin D, originating from Streptomyces parvulus (S. parvulus); then, we further focused on the anti-S. aureus ability and the omics profile of S. aureus in response to actinomycin D. The results revealed that actinomycin D had a significant inhibitory activity on S. aureus with a minimum inhibitory concentration (MIC) of 2 μg/mL and a minimum bactericidal concentration (MBC) of 64 μg/mL. Bacterial reactive oxygen species (ROS) increased 3.5-fold upon treatment with actinomycin D, as was measured with the oxidation-sensitive fluorescent probe DCFH-DA, and H2O2 increased 3.5 times with treatment by actinomycin D. Proteomics and metabolomics, respectively, identified differentially expressed proteins in control and treatment groups, and the co-mapped correlation network of proteomics and metabolomics annotated five major pathways that were potentially related to disrupting the energy metabolism and oxidative stress of S. aureus. All findings contributed to providing new insight into the mechanisms of the anti-S. aureus effects of actinomycin D originating from S. parvulus.